Some contributions of philosophy to education - Israel Scheffler (Universidad de Navarra, 2018)
Of what use is philosophy to education? What do philosophical purposes, skills and attitudes bring to educational practice? What might they accomplish? My concern in what follows is not with any particular set of philosophical doctrines, nor am I inquiring after the educational implications of this or that philosophical viewpoint. Rather, my questions pertain to philosophical activity itself. The questions are thus quite general and they are certainly not new. But they take on special urgency when viewed in the perspective of current trends that are likely increasingly to affect our future circumstances of life and our operative conceptions of education